Narratives and Alternatives for the analysis of the context of the liberation struggle in Africa: Amilcar Cabral case (Tempo e Argumento, 2021)
AbstractThis text aims to reflect on the narratives and alternative analysis regarding the context of the national liberation struggle in Guinea-Bissau, including a brief history of European colonization in Africa. The work fits into the field of history and political sociology, seeking to address the process of resistance in Portuguese Guinea, the name given to present-day Guinea-Bissau during the period of Portuguese colonialization. It also tries to analyze the political relations sewn in the colonization period built around ethnic unity and national identity in order to face Portuguese colonialization. To carry out this reflection, it was considered the Pan-Africanist perspective of Amilcar Cabral. The theoretical framework is the post-colonial thought, applied to the political processes of African countries, centered on the perspective of an essentially bibliographical study. Amilcar Cabral`s concept helped to conduct this analysis, as he was the leader of the party that managed to conquer political hegemony to lead the struggle for independence, endorsed by the various ethnic groups, neighborhood associations and other resistance groups formed by the urban elite and civil servants from large commercial enterprises in the Portuguese administration.Keywords: national liberation struggle; ethnic resistance; Guinean identity; colonialism.